Microbial growth and post-thaw quality of stallion semen cryopreserved in presence of antibiotics - Giovanni Restrepo Betancur, Giovanni (2016)
Antibiotics are used in cryopreservation of stallion semen in order to control the growth of microorganisms; however they can have negative effects on the spermatozoa. This study aimed to evaluate the effect of two antibiotic preparations on microbial growth and quality of cryopreserved stallion semen. Semen from 10 Colombian Creole horses was cryopreserved by conventional freezing with two antibiotic preparations: P1 (penicillin 10000 UI/ml and streptomycin 10 mg/ml) and P2 (penicillin 10000 UI/ml, streptomycin 10 mg/ml, and amphotericin B 25 μg/ml) and a control group without antibiotics. After thawing, computerized sperm motility evaluation, hypoosmotic test (HOS) and counting of bacteria and fungi in semen were performed. Statistical analysis was done using generalized linear models (GLM) and comparison of means by Tukey. Significant difference (p<0.05) for total motility (MT%) between P1 (32.2 ± 17.6) and P2 (34.4 ± 19.1) with the control group (39.7 ± 16.5) was found, as well as for progressive motility (MP%) between P1 (15.5 ± 14.8) with P2 (17.9 ± 16.5) and control group (19.6 ± 14.1). For microbial growth, significant difference (p<0.05) for bacteria (CFU/ml) between P1 (167.7 ± 237.1) and P2 (240.1 ± 321.0) with the control group (464.4 ± 448.5) was found. Antibiotic preparations with penicillin, streptomycin and amphotericin B on stallion semen cryopreservation reduce bacterial growth but affect post-thaw sperm motility.